2021
DOI: 10.1016/j.tcb.2020.11.001
|View full text |Cite
|
Sign up to set email alerts
|

CDK1, the Other ‘Master Regulator’ of Autophagy

Abstract: Class I phosphoinositide 3-kinase (PI3K) and mechanistic target of rapamycin complex 1 (mTORC1) signalling is inhibited during mitosis, so that autophagy and cap-dependent translation are uncoupled from nutrient availability.During mitosis, cyclin-dependent kinase 1 (CDK1) promotes phosphorylation of RAPTOR, causing dissociation of mTORC1 from lysosomes, thereby inhibiting it. CDK1 substitutes for inhibited mTORC1 by phosphorylating ATG13, ULK1, and ATG14 at canonical mTOR sites and also phosphorylates VPS34. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 82 publications
2
24
0
Order By: Relevance
“…We then found that three genes, CDK1, CCNB1, and PLK1, were included in the DHA-regulated cell cycle pathway. CDK1 (also known as CDC2), the first member of cyclin-dependent kinase family, mediates multiple pathways to regulate cell division, cell autophagy, and mitochondrial respiration (41)(42)(43). It has been proven that CDK1 is connected to poor prognosis and cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…We then found that three genes, CDK1, CCNB1, and PLK1, were included in the DHA-regulated cell cycle pathway. CDK1 (also known as CDC2), the first member of cyclin-dependent kinase family, mediates multiple pathways to regulate cell division, cell autophagy, and mitochondrial respiration (41)(42)(43). It has been proven that CDK1 is connected to poor prognosis and cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Even if a fraction of these sites is phosphorylated in vivo by other kinases, our data suggest that CDK1 can compensate, or complement the activity of these kinases to phosphorylate these sites in mitosis. Phosphorylation handover from mTOR kinase to CDK1 has been recently described to suppress autophagy in mitosis by targeting the same proline-directed sites in ATG13, ULK1, and ATG14 (Odle et al, 2021). Our data suggest that this handover is likely not limited to mTOR and other proline-directed kinases, and likely extends to non-proline directed kinases.…”
Section: Discussionmentioning
confidence: 99%
“…(Li et al, 2018). It is also known that CDK1 directly phosphorylates Raptor during mitosis promoting dissociation from the lysosome and subsequent inhibition of mTORC1 (Odle et al, 2021). TACC3, a kinase responsible for centrosome activity and microtubule assembly during cell division (Gergely et al, 2000;Peset and Vernos, 2008), phosphorylates Tuberin on S939 (Gómez-Baldó et al, 2010).…”
Section: Role Of Tuberin In the G2/m Transitionmentioning
confidence: 99%